Dominant atmospheric pollutants in malaysia - S. C. Poh; C. P. Tso (Universitas Gadjah Mada, 1985)
This Article presents a Brief of the various types of Pollutants that are contributing to the problem of air pollution in Malaysia, As well as the mention of some episodes in air pollution that have given rise to concern here